The effect of heavy atoms on the deactivation of electronic excited states of dye molecules near the surface of metal nanoparticles - Ibrayev, N.; Seliverstova, E.; Valiev, R.; Aymagambetova, A.; Sundholm, D. (Phys. Chem. Chem. Phys., 2024)
The influence of a heavy atom and the plasmon field on the efficiency of populating the lowest triplet state (T1) and on the phosphorescence intensity has been studied for fluorescein, 2Br-fluorescein, eosinand erythrosine, which have an increasing number of substituted heavy atoms. We show that the heavy atoms affect not only the rate constant of intersystem crossing (kISC) but also the rate constant of internal conversion (kIC). The calculations show that the C–H bonds in the meso position are the primary acceptors of the excitation energy of the lowest excited electronic singlet state (S1). Substitution of the meso hydrogen atoms with I or Br leads to a smaller kIC rate constant of 1 108 s 1 for fluorescein to 8 106 s 1 for eosin. Substitution with heavy atoms also leads to a larger ISC rate constant (kISC) between the T2 and S1 states because the spin–orbit coupling matrix element hS1|HSO|T2i increases by two orders of magnitude from 0.36 cm 1 for fluorescein to 35.0 cm 1 for erythrosine. The phosphorescence rate constant increases by three orders of magnitude from 4.8 10 s 1 for fluorescein to 3.3 104 s 1 for erythrosine, which is supported by experimental data. The plasmon effect increases the intensity of the xanthene dye emissions. The intensity and the quantum yield of fluorescence increase in the series fluorescein o 2Br-fluorescein o eosin o erythrosine. The intensity of the delayed fluorescence and phosphorescence grows in the same way. The enhancement factor of the phosphorescence intensity increases from 1.8 to 5.6 in the series from fluorescein to erythrosine. The differences in the plasmon effect originate from intensity borrowing to the radiative triplet–singlet transition (T1 - S0) from the singlet–singlet transitions (Sn - S0), which is more efficient when molecules have heavy atoms in the meso position.